2007
DOI: 10.1186/1471-2199-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive expression patterns of 185/333 genes in the purple sea urchin, Strongylocentrotus purpuratus: an unexpectedly diverse family of transcripts in response to LPS, β-1,3-glucan, and dsRNA

Abstract: Background: A diverse set of transcripts called 185/333 is strongly expressed in sea urchins responding to immune challenge. Optimal alignments of full-length 185/333 cDNAs requires the insertion of large gaps that define 25 blocks of sequence called elements. The presence or absence of individual elements also defines a specific element pattern for each message. Individual sea urchins were challenged with pathogen associated molecular patterns (PAMPs) (lipopolysaccharide, β-1,3-glucan, or double stranded RNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
252
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(279 citation statements)
references
References 53 publications
26
252
1
Order By: Relevance
“…Moreover, it has been found that diversification of FREPs is generated through gene conversion and point mutation [18]. Diversification of innate immune effectors has also been found in other invertebrates, leading to general reconsideration of invertebrate immune capabilities [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that diversification of FREPs is generated through gene conversion and point mutation [18]. Diversification of innate immune effectors has also been found in other invertebrates, leading to general reconsideration of invertebrate immune capabilities [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Northern blots also showed striking increases in 185/333 expression in coelomocytes from bacterially activated sea urchins compared with injury controls (9). Based on this significant increase in gene expression, 185/333 transcripts were investigated in more detail, revealing an unexpected level of sequence diversity (8,11). To date, for 185/ 333 cDNAs, 689 have been characterized from 14 sea urchins.…”
mentioning
confidence: 98%
“…To date, for 185/ 333 cDNAs, 689 have been characterized from 14 sea urchins. These sequences are predicted to encode 286 different proteins (11,12).…”
mentioning
confidence: 99%
See 2 more Smart Citations